Efekty i perspektywy międzynarodowej współpracy w dziedzinie polityki konkurencji na forum WTO - Michalski, Bartosz (Results and Perspectives of International Cooperation Undertaken by WTO Concerning Competition Policy, 2006)
Economic consequences of globalization are more and more increasing relations between the instruments of national economic policy. This article aims to present the most important reasons, results and perspectives of international cooperation concerning competition policy. They all arc related to the essential interests of each country, the European Union and also international companies. The actions taken by World Trade Organization are analyzed, which seems to be the most proper one.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (12); 2006; nr 1122, s. 33-46